The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1080/00016350510019865
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and associated factors in Mexican schoolchildren aged 6–13 years

Abstract: The objectives of the present study were to establish dental caries prevalence (percentage with caries) and experience in the primary and permanent dentition (dmft and DMFT) of 6 to 13-year-old schoolchildren in Campeche, Mexico, and to estimate the contributing roles of the likely risk indicators. A cross-sectional study was carried out in 1,644 children aged 6-13 years. Self-administered questionnaires obtained information on social, economic, behavioral, and demographic variables. The primary dentition of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
4
17

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 27 publications
6
58
4
17
Order By: Relevance
“…There was a significant relationship between dmft and the first permanent molar caries. It is simil-lar to the findings of Rosado et al (7) and Raadal et al (9) Li et al showed that children having caries in their primary teeth were three times more likely to develop caries in their permanent teeth. (10) According to the definition of dental caries as an infectious disease that can spread to other teeth, increasing the number of dental caries in primary teeth, raises the risk of caries in the permanent teeth.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There was a significant relationship between dmft and the first permanent molar caries. It is simil-lar to the findings of Rosado et al (7) and Raadal et al (9) Li et al showed that children having caries in their primary teeth were three times more likely to develop caries in their permanent teeth. (10) According to the definition of dental caries as an infectious disease that can spread to other teeth, increasing the number of dental caries in primary teeth, raises the risk of caries in the permanent teeth.…”
Section: Discussionsupporting
confidence: 65%
“…Caries experience in the primary dentition was positively associated with caries in the permanent dentition. (7) According to J. Vanobbergen et al none of the socio-demographic and behavioral variables had enough predictive power at community level to be useful in identifying caries susceptible children. (8) The aim of this study was to find whether dmft, oral hygiene and dietary habits of children with caries in permanent first molars are different from those with healthy first molars?…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with low education levels, defined as less than a high school degree, had a higher prevalence of tooth loss in a previous study (29). Similarly, in young children, the prevalence of tooth brushing was higher among the children of mothers with higher education, as compared with those born to mothers with a lower education (32). Furthermore, it has been demonstrated that the type of school (middle or high) and school grade may affect the oral health behavior of adolescents (24).…”
Section: Discussionmentioning
confidence: 86%
“…Sin embargo, en ellos no se midieron de la misma forma las lesiones de caries. Igualmente, es inevitable resaltar la baja presencia de dientes restaurados (< 10% de los índices ceod/CPOD), común en países en vías de desarrollo (6,(30)(31)(32), lo que de una manera u otra refleja o podría estar reflejando, por un lado, la nula importancia que tiene la salud bucal en la población, en este caso entre las madres/tutores de los niños, al igual que la observada en otras poblaciones mexicanas (33) y, por otro lado, el acceso que tienen los individuos a los servicios tanto curativos como de promoción de la salud bucal. Sin embargo, es necesario destacar que en la dentición primaria las lesiones no cavitadas representaron menos de 40% del componente "dientes cariados", pero en la dentición permanente se observaron resultados distintos; las lesiones no cavitadas fueron el mayor porcentaje de ese componente (> 60%).…”
Section: Discussionunclassified
“…En 1997 en Campeche, Casanova y cols. reportaron por su parte un promedio de más de tres dientes afectados y una prevalencia de poco más de 80% en la dentición permanente de los niños de 12 años de edad (6). En ese mismo estado y año, Vallejos y cols.…”
unclassified